5-fluorouracil and other fluoropyrimidines in colorectal cancer: Past, present and future - Vodenkova, Sona; Buchler, Tomas; Cervena, Klara; Veskrnova, Veronika; Vodicka, Pavel; Vymetalkova, Veronika (Pharmacology & therapeutics, 2020)
5-Fluorouracil (5-FU) is an essential component of systemic chemotherapy for colorectal cancer (CRC) in the palliative and adjuvant settings. Over the past four decades, several modulation strategies including the implementation of 5-FU-based combination regimens and 5-FU pro-drugs have been developed and tested to increase the anti-tumor activity of 5-FU and to overcome the clinical resistance. Despite the encouraging progress in CRC therapy to date, the patients' response rates to therapy continue to remain low and the patients' benefit from 5-FU-based therapy is frequently compromised by the development of chemoresistance. Inter-individual differences in the treatment response in CRC patients may originate in the unique genetic and epigenetic make-up of each individual. The critical element in the current trend of personalized medicine is the proper comprehension of causes and mechanisms contributing to the low or lack of sensitivity of tumor tissue to 5-FU-based therapy. The identification and validation of predictive biomarkers for existing 5-FU-based and new targeted therapies for CRC treatment will likely improve patients' outcomes in the future. Herein we present a comprehensive review summarizing options of CRC treatment and the mechanisms of 5-FU action at the molecular level, including both anabolic and catabolic ways. The main part of this review comprises the currently known molecular mechanisms underlying the chemoresistance in CRC patients. We also focus on various 5-FU pro-drugs developed to increase the amount of circulating 5-FU and to limit toxicity. Finally, we propose future directions of personalized CRC therapy according to the latest published evidence.
Keywords: kolorektální nádory; Animals; 5-fluorouracil; lidé; Colorectal Neoplasms; prekurzory léčiv; protinádorové látky; 5-fluorouracil pro-drugs; Drug resistance; Fluorouracil; Prodrugs; Humans; Oral fluoropyrimidines; fluoruracil; Antineoplastic Agents; Chemoresistance; zvířata; Colorectal cancer